1999
DOI: 10.1055/s-0037-1614410
|View full text |Cite
|
Sign up to set email alerts
|

APC-resistance Is a Risk Factor for Postoperative Thromboembolism in Elective Replacement of the Hip or Knee – A Prospective Study

Abstract: SummaryPostoperative venous thromboembolic complications are commonly seen after total replacement of the hip or knee. Recently, an inherited defect with resistance to the anticoagulant activity of activated protein C (APC-resistance) has been detected. APC-resistance seems to be a common risk factor, especially in Sweden, and it increases the propensity for venous thrombosis. This study assesses the prevalence of APC-resistance in a general population and its clinical significance for patients undergoing surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 19 publications
0
46
0
1
Order By: Relevance
“…Our findings confirm the findings by Tripodi et al [24], that hypercoagulability is linked to the presence of CLD. PVT and factor V Leiden corresponds to the actual prevalence of this mutation in Scandinavia [25]. As this mutation is very common and raises the risk for thrombosis about 3-fold [26], we did not adjust the thrombin generation results for this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirm the findings by Tripodi et al [24], that hypercoagulability is linked to the presence of CLD. PVT and factor V Leiden corresponds to the actual prevalence of this mutation in Scandinavia [25]. As this mutation is very common and raises the risk for thrombosis about 3-fold [26], we did not adjust the thrombin generation results for this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in Groups A (potent anticoagulants) and C (warfarin) did not receive pneumatic compression or aspirin after surgery. In five of the publications [8,14,34,37,49], the type of anesthetic was not specified for Group A (potent anticoagulants) or C (warfarin). In publications in which anesthesia was identified, 36% (3785 of 10,437) of patients in Group A (potent anticoagulants) and 29% (397 of 1342) of patients in Group C (warfarin) received spinal or epidural anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Three groups did not find an association between the presence of factor V Leiden mutation and symptomatic DVT with and without PE or isolated PE after THA or TKA [8,31,41]. In contrast to these authors, Lindahl et al [20] investigated 645 patients after THA or TKA and estimated an OR of 5.0 (95% CI, 1.9-12.9) for the association between activated protein C and symptomatic postoperative DVT. Recently, Baba-Ahmed et al [5] reported an association (OR, 10.5; 95% CI, 1.3-86) between factor V Leiden mutation and symptomatic DVT and/or PE in patients who underwent major orthopaedic surgery, including THA.…”
Section: Discussionmentioning
confidence: 99%
“…For other genetic markers, such an association is suspected and discussed controversially, eg, methylenetetrahydrofolate reductase (MTHFR) C677T and/or A1298C and plasminogen activator inhibitor 1 (PAI-1) 4G/5G polymorphisms [1-3, 10, 11, 16, 22, 30, 32, 34, 37, 44]. Results of former studies are conflicting regarding whether the single or combined presence of such genetic mutations may further increase the already very high risk for DVT after major orthopaedic surgery, justifying costly preoperative screening and additional antithrombotic prophylactic measures in these patients [5,6,8,18,20,21,23,29,31,36,[40][41][42][43]. One reason for the conflicting results may be found in the different clinical end points set in the studies varying among venographically diagnosed DVT, clinically symptomatic DVT with or without PE, or symptomatic PE only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation